The impact of perceived online service quality on swift guanxi: Implications for customer repurchase intention. Issue 2 (4th April 2018) - Shi, Si; Mu, Ren; Lin, Lin; Chen, Yang; Kou, Gang; Chen, Xue-Jiao
Abstract : Purpose: The purpose of this paper is to investigate the impact of online service quality on swift guanxi that influences customer repurchase intention and the moderating role of gender in the relationship between online service quality and swift guanxi . Design/methodology/approach: Based on survey data obtained from 274 college students, structural equation modeling was used to test the research hypotheses. Findings: The results show that the dimensions of online service quality (i.e. perceived control, convenience and customer service) are positively related to buyer-seller swift guanxi, which influences repurchase intention. Additionally, men are driven mainly by perceived control and service convenience when establishing swift guanxi, whereas women care more about customer service. Originality/value: Online service quality is the key factor underlying customer repurchase intention. In addition, gender differences exist in many aspects of online shopping including information processing, perceived service, and perceived risk. This is one of the first empirical studies that empirically examine the effects of three dimensions of online service quality on swift guanxi and take gender differences into consideration. Based on the conceptual and empirical evidence, this study provides the practical and theoretical implications of these findings.